2010
DOI: 10.1128/mcb.01566-09
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of CK2β in Embryonic Neural Stem Cells Compromises Proliferation and Oligodendrogenesis in the Mouse Telencephalon

Abstract: Genetic programs that govern neural stem/progenitor cell (NSC) proliferation and differentiation are dependent on extracellular cues and a network of transcription factors, which can be regulated posttranslationally by phosphorylation. However, little is known about the kinase-dependent pathways regulating NSC maintenance and oligodendrocyte development. We used a conditional knockout approach to target the murine regulatory subunit (beta) of protein kinase casein kinase 2 (CK2␤) in embryonic neural progenitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 43 publications
1
60
0
1
Order By: Relevance
“…However, targeted disruption of the CK2 regulatory subunit CK2β in embryonic stem cells does recapitulate some features of the Olig2-null mouse including compromised neural progenitor cell proliferation and oligodendrogenesis (Huillard et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…However, targeted disruption of the CK2 regulatory subunit CK2β in embryonic stem cells does recapitulate some features of the Olig2-null mouse including compromised neural progenitor cell proliferation and oligodendrogenesis (Huillard et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Huillard et al showed that a murine OLIG2 protein fragment containing the ST box, fused to glutathione S-transferase, was a substrate for the serine–threonine protein kinase CK2 104 . Tryptic peptide digests revealed phosphorylation of the OLIG2 fragment at residues Ser85 and Ser87 within the ST box.…”
Section: Post-translational Modificationsmentioning
confidence: 99%
“…There is some indication that CK2 plays a role in spermatogenesis [8,7,23] as well as during certain stages of embryogenesis [24,25]. Furthermore, it was shown by several groups that CK2 seems to be an important protein kinase for a variety of different cellular processes in developing organs and organogenesis [5,6,26,27]. In the differentiation of pre-adipocytes into adipocytes, CK2 was found to be accompanied by a decrease in the protein level and in the kinase activity [28,29].…”
mentioning
confidence: 99%